The Impact of Employee Satisfaction, Performance, and Resource Management on Financial Performance in Higher Education Institutions - Lasmiatun, Lasmiatun; Hardiwinoto, Hardiwinoto; Novita, Mona (JURNAL AL-TANZIM, 2025)
This study aims to analyze the influence of employee satisfaction, employee performance, and resource management on the financial performance of universities. This study uses a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (PLS-SEM), which allows the analysis of complex relationships between latent variables. Data was collected through a survey of 143 respondents consisting of employees (Educators and Education Personnel), then analyzed to test the direct influence of each variable on financial performance. The results showed that employee satisfaction (p = 0.004) and employee performance (p = 0.003) had a significant positive effect on financial performance. In contrast, resource management showed no significant direct influence (p = 0.352), although it made a substantial contribution in the structural model (f² = 0.352). These findings indicate that the human aspect is more dominant in influencing the financial performance of institutions. The implications of these results emphasize the importance of an integrated human resource management strategy, with a focus on improving employee satisfaction, performance, and empowerment to support operational efficiency and financial sustainability in the higher education environment.